Modern Spectroscopic Techniques and Applications - Khan, Maaz; Morari do Nascimento, Gustavo; El-Azazy, Marwa (IntechOpen, 2020)
Modern spectroscopic techniques have a number of applications in many fields including material science, physics, chemistry, biology, and medicine. This book, "Modern Spectroscopic Techniques and Applications", presents knowledge about these techniques and their applications. The chapters cover many aspects such as an introduction to atomic microscopy, Raman spectroscopy, infrared spectroscopy and their applications covering both the experimental and theoretical aspects. This book is aimed to provide understanding about modern spectroscopic techniques and their applications to students, scientists, and engineers working in the relevant areas.